Integrating digital and narrative medicine in modern healthcare: a systematic review - Efthymia Efthymiou (Medical Education Online)
The increasing integration of digital technologies in healthcare, such as electronic health records, telemedicine, and diagnostic algorithms, improved efficiency but raised concerns about the depersonalization of care. Narrative medicine has emerged as a pedagogical and clinical response to this shift, emphasizing the value of patient stories, socio-cultural contexts, and reflective practice. Understanding how digital tools support, rather than undermine, narrative competencies is critical for developing a more human-centered healthcare education. This review systematically examined empirical and theoretical studies on the integration of digital technologies and narrative medicine within healthcare education. Databases including PubMed, MEDLINE, and Google Scholar were searched using defined inclusion and exclusion criteria. Studies were screened, reviewed, and thematically analyzed to identify patterns in outcomes, pedagogical applications, and integration strategies.The findings indicate that narrative medicine nurtures empathy, communication, and professional identity formation among healthcare trainees. Digital tools, such as virtual reality simulations, mobile health applications, and e-portfolios, reinforce these outcomes by providing immersive, interactive, and reflective learning experiences. The integration of narrative methods into digital platforms and curricular models provides a promising approach for linking clinical competence with relational care. The convergence of digital and narrative medicine provides a compelling pedagogical framework for healthcare education. This integrated approach supports technological proficiency and humanistic values, for advancements in digital health to improve rather than displace the interpersonal foundations of patient care. Further empirical research might assess long-term outcomes and guide implementation into curricula, faculty development, and institutional policy.Background: The increasing integration of digital technologies in healthcare, such as electronic health records, telemedicine, and diagnostic algorithms, has improved efficiency but raised concerns about the depersonalization of care. Narrative medicine has emerged as a pedagogical and clinical response to this shift, emphasizing the value of patient stories, socio-cultural contexts, and reflective practice. Objective: To understand how digital tools can support, rather than undermine, narrative competencies and contribute to a more human-centered healthcare education. Methods: This review systematically examined empirical and theoretical studies on the integration of digital technologies and narrative medicine within healthcare education. Databases including PubMed, MEDLINE, and Google Scholar were searched using defined inclusion and exclusion criteria. Identified studies were screened, reviewed, and thematically analyzed to extract patterns in outcomes, pedagogical applications, and integration strategies. Results: The findings indicate that narrative medicine nurtures empathy, communication, and professional identity formation among healthcare trainees. Digital tools, including virtual reality simulations, mobile health applications, and e-portfolios, reinforce these outcomes by providing immersive, interactive, and reflective learning experiences. Integrating narrative methods into digital platforms and curricular models presents a promising approach for linking clinical competence with relational care. Conclusion: The convergence of digital and narrative medicine offers a compelling pedagogical framework for healthcare education. This integrated approach supports both technological proficiency and humanistic values, enabling advancements in digital health to enhance rather than displace the interpersonal foundations of patient care. Further empirical research is needed to assess long-term outcomes and guide implementation in curricula, faculty development, and institutional policy.